A case of antiphospholipid antibody syndrome with Budd-Chiari and colonic ulcers complicated with gastrointestinal hemorrhage - Özer İLKGÜL and Gökhan İÇÖZ and Murat DAYANGAÇ and Yaman TOKAT and Ömer ÖZÜTEMİZ (Turkish Journal of Gastroenterology, 2019)
-